Some properties and variants of weighted sticker systems - Gan, Yee Siang; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (CESER Publications, 2013)
Sticker system has been introduced by Kari in 1998 as a model for DNA computing using the recombination behavior of DNA molecules. A sticker model is an abstract computational model which uses the Watson-Crick complementary principle of DNA molecules. A sticker operation works by using ligation and annealing operation to form a complete double stranded DNA sequence. In this paper, a new variant of sticker systems, called weighted sticker systems, is introduced. Some basic properties of language families that are generated by the weighted sticker systems are investigated. This paper also introduces some restricted weighted variants of sticker systems such as weighted one-sided, regular, simple, simple one-sided and simple regular sticker systems. Moreover, the paper shows that the presence of weights increases the generative powers of usual variants of sticker systems.